Reproduction biology of the clupeid. Gonialosa manmina (Hamilton, 1822) from the Kaptai Lake Bangladesh (Chittagong University Journal of Biological Sciences, 2013)
Gonialosa manmina was found to spawn once in a year from February to July in the Kaptai Lake. The fish was found to attain sexual maturity at 80 mm total length. Sex ratio of male and female was 1:2.39 (?2 = 26.25, df = 1, P